The Psychological Emptiness Scale: a psychometric evaluation - Shona Joyce Herron; Rob Saunders; Fabio Sani; Janet Feigenbaum (BJPsych Open, 2024)
Background Feelings of emptiness are commonly reported as deeply distressing experiences. Despite established relationships between emptiness and many mental health difficulties, alongside self-harm and suicide, further study into this phenomenon has been restricted by vague definition and clinical measures with limited utility. Recently the first definition validated by individuals with lived experience of emptiness has been conceptualised, providing an opportunity to create a new measure of emptiness.